Customer satisfaction with hypermarket fresh food’s characteristics / A.R. Azhar … [et al.] - Azhar, A.R.; Mohd Salehuddin, M. Z.; Saiful Bakhtiar, Mohd Faeez; Kamaruddin, Mohd Syaquif Yasin (Universiti Teknologi MARA Cawangan Selangor, 2012)
The Malaysian food retailing industry is experiencing tremendous growth from the evolving modern fresh food retail outlets such as supermarkets and hypermarkets. This evolving pattern is influenced by the changing behaviour and lifestyle of local consumers, thus impacting on the way consumers purchase their food. Using a quantitative research approach, this paper examined customers’ satisfaction with fresh food attributes in hypermarkets. Through a self reported questionnaire, 387 respondents were approached using a convenience sampling method. It was discovered that the majority of them are satisfied with the overall quality of fresh food products. On the other hand, they are slightly satisfied with the price and availability of fresh foods in the hypermarket. Overall, an understanding of the importance of fresh food attributes is crucial as it impacts tremendously on the customer’s satisfaction.